12/10‐Helix in Mixed β‐Peptides Alternating Bicyclic and Acyclic β‐Amino Acids: Probing the Relationship between Bicyclic Side Chain and Helix Stability. Issue 70 (15th November 2018) - Simon, Matthieu; Milbeo, Pierre; Liu, Hongtao; André, Christophe; Wenger, Emmanuel; Martinez, Jean; Amblard, Muriel; Aubert, Emmanuel; Legrand, Baptiste; Calmès, Monique
Abstract: 12/10‐Helices constitute suitable templates that can be used to design original structures. Nevertheless, they often suffer from a weak stability in polar solvents because they exhibit a mixed hydrogen‐bond network resulting in a small macrodipole. In this work, stable and functionalizable 12/10‐helices were developed by alternating a highly constrained β 2,  3,  3 ‐trisubstituted bicyclic amino acid ( S )‐1‐aminobicyclo[2.2.2]octane‐2‐carboxylic acid (( S )‐ABOC) and an acyclic substituted β‐homologated proteinogenic amino acid (l ‐β 3 ‐hAA). Based on NMR spectroscopic analysis, it was shown that such mixed β‐peptides display well‐defined right‐handed 12/10‐helices in polar, apolar, and chaotropic solvents; that are, CD3 OH, CDCl3, and [D6 ]DMSO, respectively. The stability of the hydrogen bonds forming the C10 and C12 pseudocycles as well as the benefit provided by the use of the constrained bicyclic ABOC versus typical acyclic β‐amino acids sequences when designing 12/10‐helix were investigated using NH/ND NMR exchange experiments and DFT calculations in various solvents. These studies showed that the β 3 ‐hAA/( S )‐ABOC helix displayed a more stable hydrogen‐bond network through specific stabilization of the C10 pseudocycles involving the bridgehead NH of the ABOC bicyclic scaffold. Abstract : Enhanced helix stabilization : The incorporation of a bridged bicyclic amino acid ( S )‐ABOC scaffold in mixed acyclic β‐peptide sequences led to highly stable functionalizable 10/12‐helices through specific stabilization of the C10 pseudorings (see figure).